Subacute Thyroiditis and HIV Infection in A Male Patient: A Rare Case Report - Wiraanjani, Ni Putu Belinda; Erawan, Igna Tresna (International Journal of Psychology and Health Science, 2025)
Subacute thyroiditis (SAT) is an inflammatory disorder of the thyroid gland, primarily characterized by pain and commonly attributed to viral infections. However, its occurrence in individuals with HIV is exceedingly rare, with only a limited number of documented cases exploring the association between SAT and HIV. This report presents a case of SAT in a patient diagnosed with HIV. Case Report: A 32-year-old male presented with anterior neck pain and swelling, subsequently diagnosed with SAT in the context of HIV infection. Discussion: The patient reported symptoms of anterior neck pain and swelling. Thyroid ultrasonography demonstrated a hypoechoic appearance with right thyroid gland enlargement, while fine-needle aspiration biopsy (FNAB) revealed histomorphological findings consistent with SAT. Several factors may contribute to SAT, including immunosuppression associated with HIV/AIDS. HIV-induced immune dysfunction increases susceptibility to opportunistic infections, which may act as potential triggers for SAT. Conclusion: HIV infection plays a role in the pathogenesis of thyroiditis both directly and indirectly, through immune system impairment and predisposition to secondary infections.